Heart rate variability during high-intensity field exercise in female distance runners - Sumi, K.; Suzuki, S.; Matsubara, M.; Ando, Y.; Kobayashi, F. (Scandinavian Journal of Medicine & Science in Sports, 2006)
The purposes of this study were to demonstrate the transition of heart rate variability (HRV) during trials in the field and to examine the relationship between peak frequency of high-frequency band (HF) and stride frequency. Ten healthy long-distance college female runners (age 19-21 years) performed a 3000 m realistic time trial. The time-series power spectrum analysis by maximum entropy method was used to evaluate cardiac autonomic nervous activity during the race. Cross-correlation coefficients were calculated to estimate the degree of linear co-ordination between the central peak frequency of HF and stride frequency. Just after starting, the decrease in HF (0.15-1.00 Hz) and a transient increase of low-frequency band (LF)/HF were found. After that, the HF remained at a low level and LF/HF decreased sharply. These findings suggested that the parasympathetic activity was suppressed and sympathetic activity increased just after starting, and the sympathetic activity reached the saturated level according to continuation of high-intensity exercise. In spite of the significant decrease of HRV during trials, peak frequency of HF could be differentiated clearly. The cross-correlation coefficient of peak frequency of HF and stride frequency was from 0.703 to 0.868. This finding indicated that exercise rhythm reflected HRV during high-intensity running in the field.